Assessing the welfare impact of foot disorders in dairy cattle by a modeling approach - M.R.N. Bruijnis; B. Beerda; H. Hogeveen; E.N. Stassen (Animal, 2012)
Foot disorders are the main cause of dairy cow lameness and are considered to have a major impact on the welfare of dairy cattle. This study adopts a modeling approach, using a dynamic stochastic model, to provide more insight into the welfare impact of different types of foot disorders, both clinical and subclinical. The impact of specific foot disorders on welfare was assessed by simulating the incidence and duration of foot disorders and the pain associated with them. Pain assessment was based on locomotion scores, with underlying knowledge obtained from scientific literature and experts. The results demonstrated the seriousness of the welfare impact of foot disorders. The negative welfare impact was measured on a scale from 0 to 60, where the maximum outcome represents a cow having very severe pain during the whole year. On average, each cow achieves a welfare impact score of 12, which is 20% of the maximum welfare impact score. This welfare score equals having severe pain for a period of 3 months, indicating a serious impact on welfare. On average, digital dermatitis impacts most on welfare, which is caused by a high incidence of the painful clinical stage, followed by sole hemorrhages (SoH) and interdigital dermatitis and heel horn erosion (IDHE). The combination of a high incidence and long duration of SoH and IDHE causes this relatively high welfare impact of foot disorders that occur mostly subclinically. On average, over 1 year, 46% of the welfare impact due to foot disorders is caused by clinical foot disorders. The fact that subclinical foot disorders contribute more or less equally to the effects on welfare as clinical ones, indicates that farmers may readily underestimate the welfare impact by a factor two. Modeling welfare impact at cow level, individual cases of foot disorders, stresses the importance of pain intensity, indicating the importance of clinical foot disorders. This study demonstrated the serious welfare impact of foot disorders in dairy cattle and pointed out the considerable impact of subclinical foot disorders. Furthermore, the approach of welfare assessment, for example herd v. cow level, influenced the ranking of foot disorders for their impact on animal welfare. Potentially, this leads to different prioritization of specific solution strategies for dairy farmers, for example, focusing on cow comfort, hygiene or preventive medical treatments, foot trimming and/or health monitoring. The findings in this study support in raising awareness about this welfare issue.